Inhibition of Proliferation by Knockdown of Transmembrane (TMEM) 168 in Glioblastoma Cells via Suppression of Wnt/β-Catenin Pathway - Xu, Jie (Oncol Res, 2019)
Human glioblastoma multiforme (GBM) accounts for the majority of human brain gliomas. Several TMEM proteins, such as TMEM 45A, TMEM 97, and TMEM 140, are implicated in human brain gliomas. However, the roles of TMEM168 in human GBM remain poorly understood. Herein we found that mRNA levels of TMEM168 were overexpressed in GBM patients (n = 85) when compared with healthy people (n = 10), which was also supported by data from The Cancer Genome Atlas (TCGA). Kaplan–Meier analysis of Gene Expression Omnibus dataset GSE16011 suggested that enhanced TMEM168 expression was associated with shorter survival time. To investigate whether and how TMEM168 functioned in the tumorigenesis of human GBM cells, two human GBM cell lines (U87 and U373) were used for study. Lithium chloride (LiCl), an activator for Wnt/β-catenin pathway, was used for the treatment. Our data suggested that siRNA-TMEM168 (siTMEM168) prevented viability of U87 and U373 cells, induced cell cycle arrest (G(0)/G(1) phase) and promoted apoptosis, and the mechanisms involved in blocking Wnt/β-catenin pathway, as evidenced by reducing expression of β-catenin, C-myc, cyclin D1, and survivin. Furthermore, the inhibited effect of siTMEM168 on human GBM cell growth was significantly alleviated with additional LiCl treatment, substantiating the involvement of the Wnt/β-catenin pathway in this process. In summary, our data demonstrated that TMEM168 may represent a therapeutic target for the treatment of human GBM.